Geschichte des Altertums - Meyer, Eduard. (Stuttgart ; Berlin Stuttgart ; Berlin Stuttgart Stuttgart ; Berlin)
<5> cilt (1,1. c. xii, 250 sayfa ; 1,2. c. xxviii, 894 sayfa, [1] katlı tablo ; 3. c. xiv, [2], 691 sayfa, [1] katlı harita ; 4. c. xii, 666 sayfa ; 5. c. x, 584 sayfa)